Alcohol-related driving in China: Countermeasure implications of research conducted in two cities. (October 2016) - Jia, Keqin; Fleiter, Judy; King, Mark; Sheehan, Mary; Ma, Wenjun; Lei, Jing; Zhang, Jianzhen
Highlights: This paper synthesises results from studies of drink driving in two cities in China. General drivers, drunk drivers and police in Yinchuan and Guangzhou were sampled. Although the legal limits had recently been changed, levels of knowledge were low. Alcohol misuse was evident, especially among convicted offenders. A range of education, enforcement and policy measures are recommended. Abstract: Objective: Drunk driving (blood alcohol concentration (BAC) 80 mg/100 ml) was upgraded to become a criminal offence under China's Criminal Law in May 2011. While this had a major road safety benefit, there was still a high level of alcohol related crashes and fatalities. This paper develops recommendations based on a programme of research undertaken in 2012 that examined the perceptions of general motor vehicle drivers, convicted drunk driving offenders and traffic police about drinking and driving and law enforcement in the cities of Guangzhou and Yinchuan. Alcohol misuse problems were also explored using the Alcohol Use Disorders Identification Test (AUDIT). This paper integrates the findings to examine existing problems in alcohol management, law enforcement, education and rehabilitation and provides recommendations for addressing alcohol-related driving in China. Methods: A multi-study cross-sectional research programme was conducted in two Chinese cities involving general drivers, drunk driving offenders and traffic police. In total, 16 traffic police officers were interviewed and 105 traffic police officers were surveyed. In addition, 207 drunk driving offenders in detention facilities and 802 general motor vehicle drivers were surveyed. Results: Traffic police resources including human resources and facilities such as breathalysers were reported as insufficient in both cities. There were problems reported in the process of law enforcement, and shortcomings in police knowledge of factors involved in drink/drunk driving and in the practice of conducting breath alcohol testing (BAT). Knowledge about legal BAC levels and how to keep under the legal limit was very low among general motor vehicle drivers and drunk driving offenders. Proportions with alcohol misuse problems in the two driver groups were high, especially among offenders. Conclusions: Recommendations to manage alcohol-related driving are proposed for the three groups of traffic police, general motor vehicle drivers and drunk driving offenders. In particular, traffic police resources need to be improved and further education provided to police on the general deterrence potential of BAT. There should be enhanced community education and publicity to improve knowledge of drink driving regulations and how to avoid breaking the law. Alcohol misuse problems should be addressed, particularly for drunk driving offenders.